1996
DOI: 10.1021/jp9615161
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Kinetics and Reverse Saturable Absorption of Meso-Substituted Tetrabenzoporphyrins

Abstract: The mechanism of reverse saturable absorption of meso-substituted tetrabenzoporphyrins was studied by means of picosecond transient spectroscopy. Characteristic 1 (π,π*), 3 (π,π*), and (d,d) transitions have been observed. The kinetics of the excited states vary with metal substitution. The nonlinear transmission of benzoporphyrins was measured, and the excited-state absorption was determined to be the dominant optical limiting mechanism. The results agreed very well with a five-level model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 31 publications
3
65
0
Order By: Relevance
“…Recently, time-resolved diffraction patterns of cw ultrasonically excited crystals were obtained with a synchrotron source [7]. Other experiments have employed picosecond time-resolved x-ray diffraction to study transient lattice dynamics in metals [8], organic films [9], and impulsive strain generation and melting in semiconductors [10][11][12][13][14]. In particular Rose-Petruck et al [10] demonstrated transient ultrafast strain propagation in GaAs by laser-pump, x-ray-probe diffraction.…”
Section: (Received 28 November 2000)mentioning
confidence: 99%
“…Recently, time-resolved diffraction patterns of cw ultrasonically excited crystals were obtained with a synchrotron source [7]. Other experiments have employed picosecond time-resolved x-ray diffraction to study transient lattice dynamics in metals [8], organic films [9], and impulsive strain generation and melting in semiconductors [10][11][12][13][14]. In particular Rose-Petruck et al [10] demonstrated transient ultrafast strain propagation in GaAs by laser-pump, x-ray-probe diffraction.…”
Section: (Received 28 November 2000)mentioning
confidence: 99%
“…Highly conjugated porphyrins with a strong absorption in the far-visible/near-IR region have attracted a great level of interest in recent years due to their intrinsic value as photosensitiser for the photodynamic therapy of cancer (PDT) [1], multibit molecular-based information storage arrays [2][3][4][5][6][7], or near-IR dyes and nonlinear optical materials [8,9].…”
Section: J Heterocyclic Chem 42 503 (2005)mentioning
confidence: 99%
“…The additional requirements of a long excited-state lifetime, high resistance to degradative photochemistry, and large magnitude nonlinear optical (NLO) response have made identification of OPL candidates based on RSA for the NIR difficult. In contrast, a wide variety of optical limiting materials based upon phthalocyanine, [3][4][5][6][7][8][9][10][11] porphyrin, [12][13][14] fullerene, [15][16][17][18][19][20] carbon nanotube, 9,[21][22][23][24][25] nanoparticle, [26][27][28][29][30][31][32][33][34] and other [35][36][37][38][39][40] motifs have been identified for the visible spectral region. The limited number of potential NIR OPL materials 39,[41][42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%